Clinico-pathological and Molecular Findings in Canine Anaplasma phagocytophilum Infection and its Therapeutic Management - Das, Chandramita; sarma, kalyan; Eregowda, Chethan Gollahalli; Roychoudhury, Parimal; Bhowmik, Arindam; Rajesh , Justus Babykutty (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
A documented case of canine granulocytic anaplasmosis coupled with the molecular characterization of the etiological agent isreported for the first time in Aizawl district of Mizoram. A 4-year-old female Golden Retriever presented to a Teaching Veterinary Clinical Complex, CAU, Selesih, Mizoram showed nonspecific clinical signs such as fever and weight loss. The mostrelevant clinicopathological findings were fever, tachycardia, tachypnea, pale mucous membranes, dehydration, haemorrhage, and hind limb pain. anaemia, leukocytosis, lymphocytosis, monocytopenia, eosinopenia, and mild thrombocytopenia. Serum biochemistry indicated elevated ALT, ALP, total bilirubin, indirect bilirubin, BUN, and CRP. Urine analysis revealed proteinuria, bilirubinuria, and haematuria. The oxidative stress indices revealed decreased TAOA and SOD, and increased LPO levels. Blood smear examination revealed the presence of intracytoplasmatic inclusions in neutrophils associatedwithhigh positive serology for Anaplasmaphagocytophilum. Species-specific PCR analysis confirmed serological diagnosisof A. phagocytophilum.Data indicates that A. phagocytophilum circulates in natural environments of the northeast region of India and its prevalence in dogs could be underestimated because the clinical signs are frequently nonspecific and a certain diagnosisrequires the combination of clinicopathological and molecular assays. Pets living in this area should be regularly monitored andtreated for ectoparasites to minimize health risks for humans and pets.